Psychometric properties of neck disability index – a systematic review and meta-analysis - Saltychev, Mikhail (Taylor & Francis, 2025)
Purpose: To evaluate the data on the psychometric properties of the Neck Disability Index (NDI).
Materials and methods: Medline, Embase, PsychINFO, Web of Science, and Scopus were searched in April 2023. The random effects meta-analysis was conducted when possible.
Results: Of 492 identified records, 79 were included. 70 studies were considered to be of low risk of systematic bias. Alpha was >0.81. Pooled test-retest intraclass correlation coefficient was 0.91 (95% CI 0.90-0.93). The NDI correlations with pain rating scales varied from 0.38 to 0.89. 13 studies found the NDI to be unidimensional and 15 - two- or three-dimensional. The minimal detectable change varied from 3% to 27% and minimal clinically important difference from 5% to 33%. Pooled area under the curve was 0.74 (95% CI 0.68-0.80). Most studies have not detected floor or ceiling effect. Sex-related differential item functioning has been present in one study.
Conclusions: The NDI demonstrated good internal consistency and test-retest reliability without floor or ceiling effect. In most situations, the NDI could be considered a unidimensional scale. The NDI well correlated with the common scales of pain and disability. The minimal clinically important difference and minimal detectable change were around 15% (7.5/50 points).